Decomposition of the Role of Family in Reentry: Family Support, Tension, Gender, and Reentry Outcomes - Liu, Lin (Crime & delinquency, 2021)
A vast body of reentry research has investigated the role of family in facilitating reentry success. However, it is largely unknown whether family can both be a source of support and conflict and if so, whether these impacts are gender-specific. This study explores the heterogeneous elements that family brings to the reintegration process. Findings suggest that released prisoners’ families can bring either crime-inhibitory or criminogenic influences depending on the familial environment. Support from family members protects respondents from criminal recidivism, while strained family relationships are a significant predictor for drug use. Moreover, the detrimental effect of family tension is gender-sensitive: Females released from prison suffer an amplified risk of reentry failure under family tension. Implications for correctional programming are discussed.